“INFANT” ECONOMIES IN SOUTH-EASTERN EUROPE - Zarotiadis, Grigoris (Economic Annals, 2020)
Transition economies have responded quite differently to similar pro-cedures and foreign economic and socio-political interventions. This is partly be-cause of the exogenous (from the economic perspective) features of each country. In the present paper we focus on the economic ex-planation. Following an introductory dis-cussion of the stylized facts of the deepening segregation within the Central and Eastern European transition economies, we pro-ceed with a general equilibrium model of imperfect competition (a la Dixit-Stiglitz). We introduce (1) more than one imperfectly competitive manufacturing sectors and (2) capital as the ‘pseudo’ production factor that provokes economies of scale. Based on the abstract theoretical model, we argue that the supposed automatic, self-balancing process for closing cross-country disparities may not appear, even if the non-economic factors are neutralized. This is be-cause there is a possibility of experiencing a virtuous cycle of endogenously reinforced attraction of foreign accumulated capital. Economies that do not have the necessary features for this to happen because they start from a comparatively inferior level of development and/or due to a lack of pre-existing strong manufacturing – ‘ infant economies’ according to our proposed ter-minology – will experience an endogenous-ly justified, flatter path of development and may not find it easy to catch up with others.